Validation of a Newly Installed Secondary Independent Dose Verification System - Philip Kioko Ndonye; Samuel Nii Adu Tagoe (Journal of Medical Physics and Biophysics, 2022)
Abstract: The aim of the study was to validate a newly installed Mobius 3D (M3D) quality assurance software for use as a secondary independent dose verification system for comparison with an Eclipse treatment planning system (TPS) data of 3D conformal radiotherapy treatment (3D CRT). It is recommended that a secondary MU/dose calculation using a secondary method other than the TPS be performed. A total of 138 treatment fields resulting from 103 patients were planned on the TPS for treatment by 3D CRT. The treatment plans data created on the Eclipse TPS were then exported to the M3D independent verification system and results for both systems were compiled as the output of the M3D system. Percentage 3D Gamma passing rate, mean PTV and OAR dose, the percentage difference between PTV and OAR dose for both systems were generated on the M3D secondary system and the results analyzed. The 3D Gamma passing rates for the 138 patient fields verified had been analyzed graphically and had a mean gamma passing rate of 98.7±0.6 %.  For a treatment plan verification to be acceptable, a minimum gamma passing rate of 95% needs to be achieved. The percentage Gamma passing rates for the patients were well above the minimum acceptable limit of 95% as seen on the graphical results. 3D Gamma passing rates for the 138 patient treatment fields analyzed and verified had a mean passing rate of 98.7±0.6 % which was well above the minimum acceptable limit of 95% and in agreement with published data. The PTV and OAR data for the percentage difference between M3D and TPS were within Action and Tolerance levels determined and thus the M3D system was validated as a secondary independent treatment plans checker for the Eclipse TPS treatment plans at the institution.